Konsep Dasar dan Transformasi Historis Studi Hadis Tematik dalam Kajian Ilmu Hadis - Halawatul Kamala; Muhammad Alif; Mus'idul Millah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
In the modern era, approaches to understanding hadith have undergone significant transformations, necessitating more systematic and contextualized methodologies. Thematic hadith studies (mawḍū‘ī) have emerged as a methodological solution capable of integrating the Prophet’s teachings with contemporary realities in a more comprehensive manner. This research aims to examine the concept, history, and development of the thematic methodology in hadith studies. The primary focus is to explore the epistemology of this approach and its implications within modern Islamic academic discourse. This study employs a qualitative method using a library research approach. Data were collected through the analysis of primary and secondary literature, then analyzed using descriptive-analytical and historical-critical methods. The findings indicate that while the thematic method has existed since the classical era, its conceptual maturity has advanced significantly in the contemporary period. This approach has proven effective in addressing the issue of ikhtilāf al-ḥadīth, clarifying inter-narration relationships, and expanding the scope of hadith understanding according to the needs of the time. However, its main challenges include potential subjectivity in interpretation and the need for stricter methodologies in validating both sanad and matn. Therefore, thematic hadith studies serve as a bridge between classical understanding and modern academic demands. Its implications extend beyond the development of hadith science to the continued relevance of Islamic teachings in addressing contemporary intellectual and social challenges.